2012
DOI: 10.1515/hf.2011.176
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on lignin analysis by Raman spectroscopy

Abstract: Ultraviolet resonance Raman (UVRR) spectroscopy is a powerful tool for structural lignin analysis in situ: modification or isolation of lignin from biomass is not necessary. UVRR spectroscopy is equally applicable for samples with high lignin content and those with very low lignin content. Monomeric phenolic lignin model compounds and wood pulp samples have been studied at neutral and alkaline pH with UVRR spectroscopy. Concentration of guaiacol correlated well with the relative Raman band intensity, which ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Ultraviolet (UV) and resonance Raman (RR) spectroscopy have routinely been used for lignin analysis since lignin exhibits an UV absorption peak [105][106][107][108][109][110][111][112][113][114][115]. Beech and pine lignin radicals, key intermediate species in lignin biosynthesis, were measured using Kerr-gated RR spectroscopy [105,106].…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Ultraviolet (UV) and resonance Raman (RR) spectroscopy have routinely been used for lignin analysis since lignin exhibits an UV absorption peak [105][106][107][108][109][110][111][112][113][114][115]. Beech and pine lignin radicals, key intermediate species in lignin biosynthesis, were measured using Kerr-gated RR spectroscopy [105,106].…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Previously it was reported that the pH of aqueous solutions of phenolic lignin monomers affect their Raman spectra (Warsta et al 2012). UVRR spectra of the kraft pulps confirmed that pH has a substantial effect on the Raman scattering of lignin (Fig.…”
Section: Uvrr Spectramentioning
confidence: 54%
“…2). While increasing pH appeared to increase the Raman scattering intensity of phenolic monomers (Warsta et al 2012), with the pulp samples the trend was mainly the opposite, although not always consistent. Most pulp samples (10 of 12) analyzed after wetting with 0.2 M NaOH gave slightly lower maximum intensities (normalized to the cellulose band at 1093 cm -1 ), than the same samples analyzed at pH 6.…”
Section: Uvrr Spectramentioning
confidence: 80%
See 2 more Smart Citations